The Influence of Mental Budgeting on the Decision to Buy Share by Millenials - Nursaidah, Hersa; Rimenda, Tetty (KnE Social Sciences, 2024)
Abstract. The trend of stock investment has recently gained popularity among the public, especially the millennial generation. People are interested in investing in the stock market due to its potential for high returns and passive income. However, stock investment also entails decision-making risks. Investor mental budgeting is one of the factors influencing stock purchase decisions. This behavior leads investors to categorize their investment portfolios, such as for retirement or general investment. Previous research empirically established that mental budgeting impacts investor decisions. Employing quantitative methods, this study collected primary data through questionnaires from 119 respondents categorized as millennials. The analysis employed partial least squares-structural equation modeling (SEM-PLS) and SmartPLS software version 3. The results indicated that earmarking and labeling of income and downside and upside protection significantly influence stock purchase decisions in the millennial generation. Consequently, millennials are advised to adopt a mental budgeting approach when making investment decisions. Keywords: decision investment, downside and upside protection, earmarking and labeling of income, mental budgeting, purchase decision